Selected papers of Frederick Sanger : (World Scientific, 1996)
These papers are mainly concerned with the development of methods for "sequencing" - that is, determination of the order of the amino acids in proteins and of nucleotides in RNA and DNA. In 1943 the position of only one amino acid in a protein (insulin) was known, and Sanger's first paper resulted in finding a second amino acid. In his final paper in 1982 he describes the determination of a DNA sequence of 48,502 nucleotides. The papers describe the steady improvements in techniques, and exciting biological results revealed by the sequences.